The Medicinal Chemistry of Imidazotetrazine Prodrugs - Catherine L. Moody; Richard T. Wheelhouse (MDPI AG, 2014)
Temozolomide (TMZ) is the standard first line treatment for malignant glioma, reaching "blockbuster" status in 2010, yet it remains the only drug in its class. The main constraints on the clinical effectiveness of TMZ therapy are its requirement for active DNA mismatch repair (MMR) proteins for activity, and inherent resistance through O6-methyl guanine-DNA methyl transferase (MGMT) activity. Moreover, acquired resistance, due to MMR mutation, results in aggressive TMZ-resistant tumour regrowth following good initial responses. Much of the attraction in TMZ as a drug lies in its PK/PD properties: it is acid stable and has 100% oral bioavailability; it also has excellent distribution properties, crosses the blood-brain barrier, and there is direct evidence of tumour localisation. This review seeks to unravel some of the mysteries of the imidazotetrazine class of compounds to which TMZ belongs. In addition to an overview of different synthetic strategies, we explore the somewhat unusual chemical reactivity of the imidazotetrazines, probing their mechanisms of reaction, examining which attributes are required for an active drug molecule and reviewing the use of this combined knowledge towards the development of new and improved anti-cancer agents.